Answer: 3/5
Step-by-step explanation: Using the place value chart, we can see that the decimal 0.6 is 6 tenths. So we can write 0.6 as the fraction 6/10.
Notice however that 6/10 is not in lowest terms.
So we need to divide the numerator and the denominator by the greatest common factor of 6 and 10 which is 2.
So if we divide the numerator and denominator by 2, we get 3/5.
So 0.6 can be written as the fraction 3/5 which is in lowest terms.
Image provided showing the place value chart.
The answer is a scalene triangle
Answer:
<em>i: </em>x=-2, x=1
<em>ii: </em>x=-1/2
Step-by-step explanation:
Quadratic form:
You solve <em>i </em>by using FOIL (First, Outside, Inside, Last) because it is a multiplication problem.
![(x+2)(x-1)=0](https://tex.z-dn.net/?f=%28x%2B2%29%28x-1%29%3D0)
<em>"first"</em> would be
, which would equal ![x^{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D)
<em>"outside"</em> would be
, which would equal ![-1x, or -x](https://tex.z-dn.net/?f=-1x%2C%20or%20-x)
<em>"inside"</em> would be
, which would equal ![2x](https://tex.z-dn.net/?f=2x)
<em>"last" </em>would be
, which would equal ![-2](https://tex.z-dn.net/?f=-2)
Now you need to combine the terms so that they are one after the other
![+2x-2](https://tex.z-dn.net/?f=%2B2x-2)
Combine like terms, and you should get:
![x^{2} +x-2](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2Bx-2)
i Solution
<em>You need to get the variable by itself.</em>
<em>Subtract two from both sides</em>
![x+2=0\\x=-2](https://tex.z-dn.net/?f=x%2B2%3D0%5C%5Cx%3D-2)
<em>Add one to both sides.</em>
![x-1=0\\x=1](https://tex.z-dn.net/?f=x-1%3D0%5C%5Cx%3D1)
ii Solution
<em>Add all the terms.</em>
![x+2+x-1=0\\2x+1=0\\2x=-1\\x=-\frac{1}{2}](https://tex.z-dn.net/?f=x%2B2%2Bx-1%3D0%5C%5C2x%2B1%3D0%5C%5C2x%3D-1%5C%5Cx%3D-%5Cfrac%7B1%7D%7B2%7D)
Answer: 2 2/5 is 4/5 of 3
Step-by-step explanation:
We can view that as what do we multiply 3 by to get 2 2/5 and call that value x
3x = 2 2/5
x = (2 2/5)/3
Let's turn 2 2/5 into an improper fraction... 2 2/5 = 12/5
So we have
x = (12/5)/3 = (12/5)(1/3) = 4/5
Thus 2 2/5 is 4/5 of 3
Verify: 3(4/5) = 12/5 = 2 2/5
Answer:
It’s a
Step-by-step explanation: